1988
DOI: 10.2527/jas1988.6651166x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Performance of Rams Reared with or without Females after Weaning

Abstract: The objective of this study was to determine the effect of postweaning exposure to females on the subsequent sexual performance of young rams. Twenty-five crossbred rams were reared in a group with ovariectomized females from 4.5 to 9 mo of age. Ewes were brought into estrus every 2 wk during this period. A companion group of 23 crossbred rams was not exposed to females following weaning. Four 30-min sexual performance tests were administered at 10 mo of age. Rams reared with males and females (RMF) exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
5

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 16 publications
0
21
0
5
Order By: Relevance
“…There are several factors that could affect the libido and serving capacity of males. These factors result in a great variation of sexual performance of rams: season of year, breed differences, individual rams, previous breeding experience, method of restraint of ewes and age (Katz et al 1988, Mandiki et al 1998, Advi et al 2004, Dickson and Sanford 2005, Aguirre et al 2007, Marai et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…There are several factors that could affect the libido and serving capacity of males. These factors result in a great variation of sexual performance of rams: season of year, breed differences, individual rams, previous breeding experience, method of restraint of ewes and age (Katz et al 1988, Mandiki et al 1998, Advi et al 2004, Dickson and Sanford 2005, Aguirre et al 2007, Marai et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Couttie and Hunter (1956) suggested that when young bulls were reared in isolation, many failed to respond or showed less interest in mounting when first exposed to estrual females compared to bulls raised with females. Exposure of ram lambs to ewes during the postweaning prepubertal period enhanced their sexual performance (Katz et al, 1988). Yearling rams kept close to ewes in oestrus for 6 months found to have larger testes, higher plasma testosterone levels and greater sexual activity than control rams isolated from ewes (Illius et al, 1976).…”
Section: Enhance Male Sexual Performancementioning
confidence: 97%
“…Rams, unlike cattle, and goats, are not sexually stimulated by witnessing the mounting of other sheep (4) . Exposure to females during an early age promotes sexual performance, but does not prevent that some males show homosexual preferences (5) . Based on these and other characteristics, there is enough information in the scientific literature on the subject, same that is provided in the following Sections.…”
Section: Regulación Endocrina De La Actividad Neural Y Reproductivamentioning
confidence: 99%
“…Another common practice among producers is that during weaning, generally lambs are separated by sex. However, males must have heterosexual experiences during the period from weaning to year of age, making it easier to develop the sexual preference of rams to females (instead of to males), in addition to accelerating the emergence of sexual behavior (5) . Rams without experience, who are exposed to adult females, can delay the manifestation of his normal sexual behavior for several weeks.…”
Section: Efectos De Crianzamentioning
confidence: 99%
See 1 more Smart Citation